Investigating the interplay of hematological parameters, CD markers, genetic polymorphisms, and database mutations in the IL15 gene in acute myeloid leukemia patients: Blood, CD markers, IL15 polymorphisms in AML - Azeez, Darya M.; Mohammed, Sarbaz I.; M. Hassan, Kawa; Salihi, Abbas (Cellular and Molecular Biology, 2023)
Acute myeloid leukemia (AML) is a heterogeneous malignancy characterized by the clonal expansion of myeloid precursor cells in the bone marrow. In this study, we investigated the interplay of hematological parameters, CD markers, genetic polymorphisms, and database mutations in the interleukin 15 (IL15) gene in AML patients. We enrolled 59 newly diagnosed AML patients and analyzed their bone marrow specimens using flow cytometry and molecular techniques. The hematological parameters of the AML patients revealed a significant increase in platelet count and RBC, Hb, and HCT levels compared to healthy individuals. CD marker expression analysis revealed upregulation of CD33, CD45, CD13, CD117, CD38, HLA-DR, CD15, CD64, MPO, CD34, and CD11c in AML patients. Molecular analysis showed 15 mutations in different positions of exon 8 of the IL15 gene, with the most frequent mutation being a homozygous mutation resulting from a nucleotide substitution. Additionally, 10 novel heterozygous mutations were identified in different locations of chromosome 4, with a low variant rate. Finally, database analysis of gnomAD and Mutagene revealed a high number of potential driver mutations in the IL15 gene in leukemia patients. These results provide valuable insights into the genetic and immunophenotypic characteristics of AML patients and highlight the potential role of IL15 in AML pathogenesis.